PENGARUH BEBAN KERJA DAN GAJI TERHADAP SEMANGAT KERJA PEGAWAI HONORER DILINGKUNGAN KANTOR SAMSAT PUTRI HIJAU KOTA MEDAN - Siregar, Fitri Handayani (Smart GOALS Jurnal Bisnis Digital Dan Manajemen, 2024)
The purpose of this study is to determine the influence of workload and salary on the work motivation of honorary employees at the SAMSAT Putri Hijau Office, Medan City. This research was conducted at the SAMSAT Putri Hijau Office, Medan City, with a population and sample of 48 employees. The research instrument used was a questionnaire with a Likert scale model. The prerequisite tests carried out included tests of normality, multicollinearity, and heteroscedasticity. The data analysis technique used was multiple regression analysis at a significance level of α = 0.05. The results of this study show that the workload of honorary employees (X1) has a significant effect on work motivation, with the t-value greater than the t-table value (3.333 > 1.679) and a significance value of 0.002 < 0.05. Meanwhile, salary (X2) also has a significant effect on work motivation, with the t-value greater than the t-table value (2.552 > 1.679) and a significance value of 0.014 < 0.05. Based on the SPSS output, it is known that the R-squared value is 0.230, meaning that the variance of the work motivation variable can be explained by the workload and salary variables by 23 percent, while the remaining 77 percent is explained by other variables not included in this model. In other words, there are still other independent variables that influence employee work motivation.